Multimodal Evaluation of Presumed Tuberculous Serpiginous-Like Choroiditis. (3rd October 2019) - Wang, Haoyu; Tan, Shi Zhuan; Aslam, Tariq; Jones, Nicholas P.; Steeples, Laura R.
ABSTRACT: Purpose : To evaluate multimodal imaging findings in longitudinal follow-up of a patient with presumed tuberculous serpiginous-like choroiditis (TB-SLC). Method : We evaluated multimodal imaging in a 62-year-old male with TB-SLC. Correlation between optical coherence tomography angiography (OCTA), swept-source OCT (SS-OCT) and fundus autofluorescence (FAF) at defined disease stages and evolution of observed imaging descriptors during long-term follow-up has not been previously reported. Results : OCTA of the active lesion demonstrated defined areas of choriocapillaris hypoperfusion, suggesting inflammatory vascular occlusive pathology. Over 9-month follow-up, OCTA illustrated sequential improvement in choriocapillaris flow, suggesting vascular remodeling. This correlated with progressive change in FAF signal and transition to diffuse hypoautofluorescence. SS-OCT demonstrated focal choroidal thickening and retinal pigment epithelium elevation in acute phase and resolution in time. Conclusion : Multimodal imaging, particularly novel non-invasive technologies such as OCTA and SS-OCT, improves our understanding of the pathogenesis and evolution of disease in TB-SLC.